2017
DOI: 10.1002/jmri.25878
|View full text |Cite
|
Sign up to set email alerts
|

Transcranial MRI‐guided high‐intensity focused ultrasound for treatment of essential tremor: A pilot study on the correlation between lesion size, lesion location, thermal dose, and clinical outcome

Abstract: 1 Technical Efficacy: Stage 4 J. Magn. Reson. Imaging 2017.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
34
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 45 publications
(35 citation statements)
references
References 34 publications
1
34
0
Order By: Relevance
“…Because the first publication of favorable clinical results of MRgFUS thalamotomy in 2013, 5 a few additional reports have been provided regarding its results, 10,11 technical methods, 12 adverse effects, 13 and comparative outcomes with other therapeutic modalities 14 ; however, these studies have primarily been short term. 5,6,[9][10][11]15 With this treatment, the 12-month reduction rate of total CRST was 35% to 56%, hand tremor reduction rate was 40% to 78%, and disability reduction rate was 61% to 85% ( Table 2). We have now shown a 56% reduction rate for 4-year outcome of hand tremor treatment and a 63% reduction rate for disability related to hand tremor, both of which were comparable to the 12-month outcomes.…”
Section: Four-year Results Of Mrgfus Thalamotomymentioning
confidence: 97%
See 1 more Smart Citation
“…Because the first publication of favorable clinical results of MRgFUS thalamotomy in 2013, 5 a few additional reports have been provided regarding its results, 10,11 technical methods, 12 adverse effects, 13 and comparative outcomes with other therapeutic modalities 14 ; however, these studies have primarily been short term. 5,6,[9][10][11]15 With this treatment, the 12-month reduction rate of total CRST was 35% to 56%, hand tremor reduction rate was 40% to 78%, and disability reduction rate was 61% to 85% ( Table 2). We have now shown a 56% reduction rate for 4-year outcome of hand tremor treatment and a 63% reduction rate for disability related to hand tremor, both of which were comparable to the 12-month outcomes.…”
Section: Four-year Results Of Mrgfus Thalamotomymentioning
confidence: 97%
“…MRgFUS thalamotomy has emerged as an additional option for disabling ET. Because the first publication of favorable clinical results of MRgFUS thalamotomy in 2013, a few additional reports have been provided regarding its results, technical methods, adverse effects, and comparative outcomes with other therapeutic modalities; however, these studies have primarily been short term . With this treatment, the 12‐month reduction rate of total CRST was 35% to 56%, hand tremor reduction rate was 40% to 78%, and disability reduction rate was 61% to 85% (Table ).…”
Section: Discussionmentioning
confidence: 99%
“…Imaging methods such as MRI diffusion tensor imaging tractography are under investigation to improve targeting for both FUS and DBS . Analyses of postprocedure MRI changes are also under study to improve outcome of sonication‐based ablation …”
Section: Discussionmentioning
confidence: 99%
“…A randomized sham‐controlled trial showed a 47% reduction in the tremor subscore of the Clinical Rating Scale for Tremor (CRST) 1 year after treatment . Although a recent follow‐up of this pivotal trial reported a persistent 55% reduction in dominant tremor score at 2 years, how MRgFUS compares to other techniques in the long‐term is unclear given other studies, albeit of short‐term follow‐up and smaller sample size, describe consistent lesion shrinkage and loss of effect over time …”
mentioning
confidence: 99%
“…Our primary objective is to describe the long‐term outcome in tremor reduction after MRgFUS thalamotomy with an additional goal of assessing the association between initial lesion volume and sustained benefit from treatment. Finally, few studies have examined what are predictors of treatment efficacy . We hypothesize lesion volume is associated with long‐term benefit and explore this with multivariable linear regression analysis.…”
mentioning
confidence: 99%